A comparative analysis of emotional intelligence and intelligence quotient among Saudi business students' toward academic performance. (10th October 2019) - Khan, Sania
Understanding the determinants of student learning outcomes and their academic performance is never being easy. Most of the studies examined the impact of emotional intelligence (EI) and intelligence quotient (IQ) on academic performance discretely, and their combined influence was not studied. The study identifies various dimensions of EI and IQ and investigates their impact on university business students' academic performance comparatively among private and public university students. The data relevant to this study were collected from 416 students of various Business Colleges of Saudi central province universities, using online survey questionnaire. Structural equation modeling analysis using SPSS AMOS was used to evaluate the data. The private students possess a significant IQ, and their academic performance is primarily driven by IQ and with high EI; whereas public sector students possess moderate EI with insignificant IQ levels and tend to perform average in their academics. All the measurement items of EI and IQ explained only 43.6% of variance in public student's performance and 56.3% in private student's performance. The study argues the cognitive intelligence is very purposive in academics but narrow in nature and does not extend the horizon of student's lifelong learning. Therefore, EI is vital and plays a prominent role in supporting their IQ as well. The study is limited to only business students; therefore, findings may not be generalized to other academic domains and for master level students. It suggests to conduct further studies to explore relationship among various exogenous variables.